DESAIN PERKERASAN KAKU DENGAN METODE MANUAL PERKERASAN JALAN (REVISI JUNI 2017) DI DESA MUARA IKAN – TALANG ALI KABUPATEN PALI - Sudirman; Saloma; Arie Putra Usman; Ammar Asyraf; Deby Ansyory; Siti Anisah (LATERAL: Jurnal Teknik Sipil, 2025)
Roads, as an essential part of the national transportation system, play a very vital role, especially in supporting economic, social, cultural, and environmental aspects. In road maintenance planning, it is necessary to have a well-organized and systematic road handling program. One of the steps in planning new roads is to determine the pavement thickness. The aim of this research is to determine the pavement thickness of roads in Muara Ikan Village - Talang Ali, PALI Regency, using the 2017 Manual for Pavement Design (MDP) method. By utilizing various methods and approaches related to traffic volume, vehicle types, subgrade soil types, and planning duration, pavement thickness calculations can be performed. The research method includes surveys of the geometric conditions of the road, daily traffic volume, and surrounding topography. The data obtained are further analyzed using the pavement design guidelines from 2017. The results indicate that the rigid pavement design based on the 2017 MDP method uses concrete pavement with a compressive strength of Fs’ 45 MPa and a thickness of 27.5 cm, an aggregate base layer of Class A with a thickness of 15 cm, and soil improvement using selective backfill with a thickness of 30 cm.